2016
DOI: 10.1002/jez.2021
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Performance and Functional Robustness of Movement are Linked to Muscle Architecture: Comparing Elastic and Nonelastic Feeding Movements in Salamanders

Abstract: Muscle-powered movements are limited by the contractile properties of muscles and are sensitive to temperature changes. Elastic-recoil mechanisms can both increase performance and mitigate the effects of temperature on performance. Here, we compare feeding movements in two species of plethodontid salamanders, Bolitoglossa franklini and Desmognathus quadramaculatus, across a range of body temperatures (5-25°C) to better understand the mechanism of elastically powered, thermally robust movements. Bolitoglossa ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(58 citation statements)
references
References 38 publications
3
55
0
Order By: Relevance
“…In vivo studies have found that performance of feeding behaviors that utilize elastic-recoil mechanisms is maintained despite changing temperature and the effects on muscle contractile physiology (Anderson and Deban, 2010;Anderson et al, 2014;Deban and Lappin, 2011;Deban and Richardson, 2011;Deban and Scales, 2016;Scales et al, 2016). Because these salamanders, toads and chameleons are maintaining performance at lower temperatures, their muscles must be shortening to do work with relatively low forces, provided that P 0 is affected by temperature as we have shown in the present study.…”
Section: Impacts On Elastically and Muscle-powered Movementssupporting
confidence: 56%
See 2 more Smart Citations
“…In vivo studies have found that performance of feeding behaviors that utilize elastic-recoil mechanisms is maintained despite changing temperature and the effects on muscle contractile physiology (Anderson and Deban, 2010;Anderson et al, 2014;Deban and Lappin, 2011;Deban and Richardson, 2011;Deban and Scales, 2016;Scales et al, 2016). Because these salamanders, toads and chameleons are maintaining performance at lower temperatures, their muscles must be shortening to do work with relatively low forces, provided that P 0 is affected by temperature as we have shown in the present study.…”
Section: Impacts On Elastically and Muscle-powered Movementssupporting
confidence: 56%
“…Many ectotherms bypass the limitations of muscle contraction and maintain performance at lower temperatures by using elastic-recoil mechanisms in their feeding movements (chameleons: Anderson and Deban, 2010;toads: Deban and Lappin, 2011;salamanders: Anderson et al, 2014;Deban and Richardson, 2011;Deban and Scales, 2016;Scales et al, 2016). These animals are able to use their muscles to stretch elastic connective tissue, storing energy that is later released rapidly when this tissue recoils (de Groot and van Leeuwen, 2004;Deban et al, 2007;Lappin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in temperature present a significant challenge to organisms, especially ectotherms; low temperature can result in substantial decreases in ecologically relevant performance such as predator escape and feeding (Huey and Bennett, 1987;John-Alder et al, 1989;Lutz and Rome, 1996;Wintzer and Motta, 2004;Devries and Wainwright, 2006;Herrel et al, 2007;Deban and Scales, 2016;Scales et al, 2016). Reductions in performance such as running and swimming velocities and jumping distances primarily result from lower muscle contractile rates that can decline by half over a 10°C drop in temperature (Bennett, 1984(Bennett, , 1985Hirano and Rome, 1984;Bauwens et al, 1995;Lutz and Rome, 1996;Peplowski and Marsh, 1997;Navas et al, 1999;Donley et al, 2007;Herrel et al, 2007;James, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Each epibranchial attaches rostrally to paired ceratobranchials, which then connect rostrally to the unpaired basibranchial that sits in the floor of the mouth and supports the tongue pad (Lombard and Wake, 1977;Wake and Deban, 2000;Deban, 2002). In muscle-powered, non-ballistic projection, the SAR is directly attached to the epibranchials, and little collagen is available in the SAR for energy storage (Lombard and Wake, 1977;Deban et al, 2007;Deban and Scales, 2016;Scales et al, 2016). Thus, during tongue projection, activation of the SAR coincides with tongue movement and the epibranchial does not leave the SAR (Deban and Dicke, 1999;Deban and Scales, 2016;Scales et al, 2016).…”
Section: Introductionmentioning
confidence: 99%